GRID CONNECTED SOLAR PHOTOVOLTAIC USING ANFISWITH BATTERY STORAGE, FUEL CELL INTEGRATION FOR POWER CONDITIONING (International Journal of Multidisciplinary Engineering In Current Research, 2020)
Global energy demand is accelerating daily which is resulting very hugeenergy crisis and environmental pollution has to make focus to move towards integrating renewable energy sources like solar photovoltaic (SPV), wind, fuel, etc. SPV is intermittently overcome by Battery Energy Storage System (BESS) along with fuel cell. The hybrid generation with DC-link is integrated with the SPV, Fuel cell, and battery energy storage system to maintainconstant DC link voltage. To capture maximum available solar power using an adaptive Neuro-fuzzy information system (ANFIS) based maximum power point tracking technique (MPPT). Battery Energy Storage System which is activated based on the state of charge. PI controller monitors the state of charge through a bidirectional converter. DC link is integrated with the grid through a Three-phase voltage source converter. A three-phase voltage source converter adaptive Neuro-fuzzy information system (ANFIS) is used to control volatile changes in grid parameters rising by its variable demand. Grid synchronization can be achieved when dynamics variation of load. MATLAB/Simulink software simulated under different dynamic variations in load and volatile changes in a grid linkedto the hybrid system under different supply conditions.